Characterization of the aqueous fractions from hydrotreatment and hydrothermal liquefaction of lignocellulosic feedstocks. (March 2015) - Panisko, Ellen; Wietsma, Thomas; Lemmon, Teresa; Albrecht, Karl; Howe, Daniel
Abstract: In this study the aqueous phases resulting from the hydrothermal liquefaction (HTL) of biomass and the hydrotreatment (HT) of fast pyrolysis bio-oils were analyzed via TC, COD, GC-MS, GC-FID, HPLC, and ICP-OES to determine the organic and inorganic species present and the quantitative amounts of each. This work is necessary to address a significant knowledge gap in the literature related to the aqueous phases from thermochemical processes. Results showed that water from the hydrotreatment of eight different bio-oils contained less than 1 wt% total carbon, in many cases less than 0.2%. Negligible organic carbon was observed. HTL samples contained between 1 and 2 wt% carbon. Due to the large volume of water added to the HTL feedstock and the dilute samples generated, this accounts for 34–45% of the total carbon sent to the reactor. The majority of this carbon was present as acids, with glycolic acid and acetic acid having the highest concentrations. Alcohols, specifically methanol and ethanol, were also present. Numerous ketones were observed, consisting of mainly acetone and cyclopenta-ones. The amount of the total carbon identified and quantified in the HTL samples ranged from 64 to 82%. Inorganic species present in the HT samples were sodium, silicon, and sulfur. The highest levels of sulfur were observed in the grasses and agricultural residue (corn stover). The HTL samples exhibited much higher inorganic content, with very high levels of sodium and potassium. Alkali and alkali earth metals, as well as sulfur, were also present at levels high enough to raise concerns for the use of catalysts in downstream upgrading or reforming processes. Highlights: Hydrotreatment samples are less than 1 wt% total carbon with negligible organic C. 64–82% of the total carbon in HTL samples was identified and quantified. Organic species in HTL samples were mainly acids, alcohols, and ketones. Inorganic species in HT samples were mainly Na, Si, and S. Inorganic species in HTL included Ca, K, Mg, Mn, Na, P, Si, and S.